Modeling of Spall Fracture in Brittle Solids - Basista, M. (Engineering Transactions, 1997)
This is a synthetic and critical review of the selected theories of brittle spall fracture. Since the main body of research clone on spalling can actually be credited to a few research institutions, the papers selected for this overview are classified according to their place of origin with some effort to maintain their order of appearance. Emphasis is placed on those models which were instrumental in the development of spall fracture modeling in brittle solids. Consequently, early models based on the critical stress criterion are merely recalled whereas micromechanical and phenomenological damage models of brittle spalling are discussed in more detail. The methods developed in the physics of critical phenomena (e.g. percolation theory), so far relatively unexplored in the modeling of dynamic fracture processes, are also outlined.